Developing Differentiated Learning Modules Based on Edutainment in Islamic Religious and Character Learning in Elementary Schools - Aziz, Su’udin; Ma’arif, M. Jauharul; Yulia, Nurul Mahruzah (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to develop an Edutainment-Based Differentiated Learning Module in Islamic Religious and Character Learning in Elementary Schools. This research used a Research and Development (R&D) method with an ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The analysis was carried out by analyzing student needs, then designing and developing a module by validating and revising the product. Then, the implementation and evaluation were carried out in 3 elementary schools with a sample of 100 students and analyzed qualitatively and quantitatively. After being validated by material experts, teaching material experts, language, and practitioners, this module was revised, then implemented in elementary schools in Bojonegoro, Indonesia. The results of this study indicated that the module was feasible with an assessment of material experts, teaching materials, language and practitioners with an average of 92%. The results of the student response analysis, this module was considered easier for students to learn, full of games and challenges and the material is familiar with students' abilities. The results of the student ability analysis showed that the use of the module can increase student involvement and improve student learning outcomes by 75% with a good category. This study showed that the Edutainment-Based Differentiated Learning Module was effective in increasing student engagement and learning outcomes in Islamic Religion and Character Learning in elementary schools. This module can be used as a reference for developing innovative teaching materials that are fun and in accordance with students' needs.